The Influence of Leadership, Professional Human Resources, Institutions, Community Participation, and Investment on the Effectiveness of Spatial Policies in the North Bandung Region - Jemi Tri Sonjaya (Syntax Corporation Indonesia, 2025)
This study aims to analyze the influence of leadership, professional human resources, institutions, community participation, and investment on the effectiveness of spatial planning policies in the North Bandung Region (KBU). The research method used is a quantitative approach with regression analysis to measure the relationship between variables. Data was obtained through a survey of stakeholders involved in spatial planning policies in the North Bandung area. The results of the study show that professional human resources, strong institutions, and investment have a positive and significant effect on the effectiveness of spatial planning policies. Meanwhile, leadership and community participation did not show a significant influence on policy effectiveness. This research provides important insights for spatial policy making in KBU, by emphasizing the importance of human resource capacity building, institutional strengthening, and investment management to support more effective policy implementation. In addition, these findings also reveal that while community participation and leadership are considered important, these factors require a more appropriate approach in order to have a significant impact on spatial planning policies. These findings can be the basis for policymakers to design a more holistic and sustainable strategy in spatial planning management in the North Bandung Area.